The Ethics of Mentoring - Moberg, Dennis J. (Business ethics quarterly, 2004)
Mentoring is an age-old process that continues to be practiced in most contemporary organizations. Although mentors are often heralded as virtuous agents of essential continuity, mentoring commonly results in serious dysfunctions. Not only do mentors too often exclude people different from themselves, but also the people they mentor are frequently abused in the process. Based on the conception of mentor as a quasi-professional, this paper lays out the ethical responsibilities of both parties in the mentoring process.